SPE Annual Technical Conference and Exhibition 2014
DOI: 10.2118/170698-ms
|View full text |Cite
|
Sign up to set email alerts
|

Rate Transient and Decline Curve Analyses for Continuously (Dual-Porosity) and Discretely Naturally Fractured Reservoirs

Abstract: Forecasting production rates and reserves is important for reservoir management. Analysis of long-term production data has traditionally been performed using the empirical Arps (1945) decline curves to predict future production. Fetkovich (1980) combined Arps decline curves with constant-wellbore pressure solutions to offer a new method for decline-curve analysis. Furthermore, both rate-transient and declinecurve analyses for naturally fractured reservoirs were performed using Arps (1945) decline curves or Wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 12 publications
(3 citation statements)
references
References 60 publications
0
3
0
Order By: Relevance
“…They introduced a new 'Z-factor' term and proposed a MBE similar to the conventional MBE. Kuchuk et al (2014) observed a linear drop in p/Z plots from production data of naturally fractured reservoirs, followed by a change in the slope during the latter stages. They concluded that the initial linear drop indicates a fracture depletion period and the following slope change indicates significant contribution from the matrix system.…”
Section: Introductionmentioning
confidence: 89%
“…They introduced a new 'Z-factor' term and proposed a MBE similar to the conventional MBE. Kuchuk et al (2014) observed a linear drop in p/Z plots from production data of naturally fractured reservoirs, followed by a change in the slope during the latter stages. They concluded that the initial linear drop indicates a fracture depletion period and the following slope change indicates significant contribution from the matrix system.…”
Section: Introductionmentioning
confidence: 89%
“…The mechanism driving the gas-water flow includes two aspects: (1) fracture closure and (2) expansion of the fluid (gas-water phase). Kuchuk et al [44] also considered the assumption that fracture closure and expansion of water and free gas in the fracture system drive the accumulation of natural gas and water at the surface suggesting the occurrence of pseudo-steady-state flow in fractured reservoirs.…”
Section: Materials Balance Equation (Mbe) and Diffusionmentioning
confidence: 99%
“…Carbonate reservoirs, which approximately account for 60% of the world oil reservoirs, represent a significant amount of oil and gas reserves and have a great potential to be exploited [1]. With further exploration and development, these fractured (see Figure 1(a)) and fractured-vuggy (see Figure 1(b)) carbonate reservoirs have been attracting considerable attention in recent years [2][3][4][5]. The complex structures of the reservoir are characterized by the presence of different porous media and transmissibility [6].…”
Section: Introductionmentioning
confidence: 99%